2009
DOI: 10.1007/s00792-009-0237-3
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic methane production in formation waters from a large gas field in the North Sea

Abstract: Methanogenesis was investigated in formation waters from a North Sea oil rimmed gas accumulation containing biodegraded oil, which has not been subject to seawater injection. Activity and growth of hydrogenotrophic methanogens was measured but acetoclastic methanogenesis was not detected. Hydrogenotrophic methanogens showed activity between 40 and 80 degrees C with a temperature optimum (ca. 70 degrees C) consistent with in situ reservoir temperatures. They were also active over a broad salinity range, up to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(48 citation statements)
references
References 31 publications
3
40
0
2
Order By: Relevance
“…Potential for microbial methane production Methane production was observed only in the enrichment amended with H 2 þ CO 2 , similar to earlier observations found in enrichments using formation waters from a gas field in the North Sea (Gray et al, 2009). In Abbreviation: ND, not determined.…”
Section: Microbial Cell Densitysupporting
confidence: 88%
See 1 more Smart Citation
“…Potential for microbial methane production Methane production was observed only in the enrichment amended with H 2 þ CO 2 , similar to earlier observations found in enrichments using formation waters from a gas field in the North Sea (Gray et al, 2009). In Abbreviation: ND, not determined.…”
Section: Microbial Cell Densitysupporting
confidence: 88%
“…The chemical and isotopic data have been interpreted by plotting hydrocarbon gas composition C 1 /(C 2 þ C 3 ) versus d 13 C-CH 4 (Bernard et al, 1978) and dD-CH 4 versus d 13 C-CH 4 (Schoell, 1983) on widely used conventional diagrams. Numerous microbiological approaches have also been used to understand the methane production processes in subsurface environments such as petroleum-contaminated aquifers (Gray et al, 2009), geothermal aquifers (Kimura et al, 2005;Mochimaru et al, 2007b), and coalbed aquifers (Shimizu et al, 2007;Strąpoć et al, 2008). Igari and Sakata (1989) measured stable carbon isotopic ratios of methane in natural gases associated with the accretionary prism in Southwest Japan, and concluded that the methane was of thermogenic origin.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum specific growth rate of the mixed methanogenic cultures (l max ) was calculated from the slope of the linear part of the graph of residual methane production (natural logarithm) versus time as described before (Gray et al 2009). …”
Section: Growth Ratementioning
confidence: 99%
“…Biodegradation thus reduces the gas : oil ratio of the trapped oil, and may result in the exsolution of a dry gas cap enriched in methane and CO 2 (Jones et al, 2008;Larter et al, 2005;Wenger et al, 2002). This process may offer a way to extract energy otherwise trapped in nonextractable oil (Gieg et al, 2008;Gray et al, 2009;Jones et al, 2008). Based on the conversion rates estimated from methane-producing consortia published so far, the commercial potential of the process may be significant (Berdugo-Clavijo & Gieg, 2014;Gieg et al, 2008).…”
mentioning
confidence: 99%